Philosophy of Education in view of the pressing Muslim Requirement in the Islamic and World Perspective - Khan, Muin ud Din Ahmad (IIUC Studies, 2015)
In Islam education is endemic to humanity and to the Muslims talabul ilm, acquisition cum research, is imperative, whereas by being bounded within the four walls of husulul ilm, acquisition of knowledge, education of the present-day Muslims has became epidemic by dint of their enthusiasm especially for chewing the cud of the foreign nations in the name of modernization of education which practically throws the Muslim elites out of the global Ummatic social arena turning them into supplanted personalities. Hence, in order to catching up with the dynamic spirit of Islamic education the Muslims are required to suitably overhaul the mentality and aims and objects of education. IIUC Studies Vol.9 December 2012: 79-106